The association between increasing oral anticoagulant prescribing and atrial fibrillation related stroke in Ireland. Issue 1 (28th June 2021) - Kennedy, Cormac; Gabr, Ahmed; McCormack, Joan; Collins, Rónán; Barry, Michael; Harbison, Joe
Abstract : Aims: Recent increases in the number of patients with atrial fibrillation (AF) prescribed oral anticoagulants (OAC) are evident in Ireland and internationally, largely due to the availability of direct oral anticoagulants (DOACs). This study aimed to determine the rate of stroke in the context of increasing anticoagulation utilisation, with a focus on AF‐related ischaemic stroke (IS). Methods: Dispensing data for OACs were identified for the period 2010–2018 as well as hospital discharges for IS (2005–2018). Irish National Stroke Register data were used to elucidate the characteristics of patients with acute ischaemic stroke. Results: The number of patients prescribed OACs increased by 94% from 2010–2018 with a significant change from 2013 (β = 2.57, P = .038), associated with a large increase in the number of patients on DOACs. There was 3.3‐fold increase in expenditure on OACs nationally from 2013 to 2018, of which 94% was DOAC related. Using the 2013 timepoint, ischaemic stroke rates until 2018 did not show a significant deviation from the previous trend (β = 0.00, P = .898). The percentage of AF‐related ischaemic stroke was stable from 2013 to 2017 with a 4.5% decrease in 2018. The percentage of ischaemic stroke patients with previously diagnosed AF decreased from 2013 to 2018; however, there was an increase in the percentage of ischaemic strokes while on OAC in this cohort. Conclusion: Large increases in OAC utilisation have not resulted in changes in ischaemic stroke rates at a national level. The percentage of ischaemic strokes with a previous diagnosis of AF has decreased indicating a possible benefit from greater OAC utilisation. However, the percentage presenting with an ischaemic stroke while on OAC treatment is increasing. The increase in patients presenting with stroke while treated with OAC may largely reflect the national increase in patients prescribed DOACs but the findings raise concerns about treatment failures. The real‐world effectiveness of DOACs requires further examination. Abstract :